EVALUASI KINERJA BANK PEMBANGUNAN DAERAH: CAMEL, DATA ENVELOPMENT ANALYSIS DAN STOCHASTIC FRONTIER - Sengkey, Marthen (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
Performance evaluastion is an important factor used in financial institution goal setting and management performance assessment.  Traditional tools used by banks to measure their performance are financial ratios such as CAR, profitability ratios, activity ratios etc. However, those ratios are not enough for management to evaluate business performance as a whole.  This study used DEA, SFA, and CAMEL to present a general measure of state banking performance.  The combination of these three well-known methods for bank’s performance is also supplemented by three statistical approaches such as ANOVA, Spearman rank correlation, and Tobit regression model. The aim of this study is to examine the efficiency performance of Indonesia’s regional development banks, using cross-sectional, and timel series data analyses of 26 regional development banks in Indonesia from 1994-2004 with one output variable, four input variables, and also four exogenous variables.  The output variable is total loans, and input variables are (1) total deposits, (2) total operational expenses, (3) capital, and (4) total fixed assets.  Other environmental variables (zs) are government intervention, ownership, location of banks, and ABC classification described by Central Bank of Indonesia. The result suggests that financial ratios are not enough indicators of overall bank performance.  There is no statistical significant difference between technical efficiency scores of SFA (62.8%), and DEA (38.3%).  Bank’s technical efficiency is affected by government intervention, location, ownership, and ABC classification prescribed by bank authority.  Except capital to total assets (C/TA) ratio and cash and cash placement to Central Bank and other banks to total deposits and borrowing (CPCBB/TDB) ratio, all of CAMEL ratios were found significantly associated with efficiency estimate of DEA. The original contributions of the study are as follows: Bank performance measurement by DEA and SFA. Correlates deterministic and stochastic results. Linked the CAMEL; model and DEA results to TOBIT regression.